Literature, ethics, and the emotions - Asher, Kenneth (Cambridge, 2017)
Recently there has been a renewed interest in the ethical value of literature. However, how exactly does literature contribute to our ethical understanding? Asher argues that literary scholars should locate this question in the long and various history of moral philosophy.